Pregunta
upstudy study bank question image url

Solve the following equations for \( x \). \( \begin{array}{ll}17 .) 5^{2 x}=5^{2} & 18 \\ \text { 19. }(2.5)^{2 x+1}=(2.5)^{5} & 20 \\ \text { 21. } 10^{1-x}=100 & 22 \\ \text { 23. } 3(2.7)^{5 x}=8.1 & 24 \\ \text { 25. }\left(2^{x+1} \cdot 2^{-3}\right)^{2}=2 & 26\end{array} \)

Ask by Todd Sherman. in the United States
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

The solutions to the equations are: 1. \(x = 1\) 2. \(x = 2\) 3. \(x = -1\) 4. \(x = 0.2\) or \(x = 0.2\) 5. \(x = 2.5\)

Solución

Solve the equation \( 5^{2x}=5^{2} \). Solve the equation by following steps: - step0: Solve for \(x\): \(5^{2x}=5^{2}\) - step1: Set the exponents equal: \(2x=2\) - step2: Divide both sides: \(\frac{2x}{2}=\frac{2}{2}\) - step3: Divide the numbers: \(x=1\) Solve the equation \( (2.5)^{2x+1}=(2.5)^{5} \). Solve the equation by following steps: - step0: Solve for \(x\): \(2.5^{2x+1}=2.5^{5}\) - step1: Set the exponents equal: \(2x+1=5\) - step2: Move the constant to the right side: \(2x=5-1\) - step3: Subtract the numbers: \(2x=4\) - step4: Divide both sides: \(\frac{2x}{2}=\frac{4}{2}\) - step5: Divide the numbers: \(x=2\) Solve the equation \( 10^{1-x}=100 \). Solve the equation by following steps: - step0: Solve for \(x\): \(10^{1-x}=100\) - step1: Rewrite in exponential form: \(10^{1-x}=10^{2}\) - step2: Set the exponents equal: \(1-x=2\) - step3: Move the constant to the right side: \(-x=2-1\) - step4: Subtract the numbers: \(-x=1\) - step5: Change the signs: \(x=-1\) Solve the equation \( 3(2.7)^{5x}=8.1 \). Solve the equation by following steps: - step0: Solve for \(x\): \(3\times 2.7^{5x}=8.1\) - step1: Convert the expressions: \(3\left(\frac{27}{10}\right)^{5x}=8.1\) - step2: Multiply by the reciprocal: \(3\left(\frac{27}{10}\right)^{5x}\times \frac{1}{3}=8.1\times \frac{1}{3}\) - step3: Multiply: \(\left(\frac{27}{10}\right)^{5x}=\frac{27}{10}\) - step4: Set the exponents equal: \(5x=1\) - step5: Divide both sides: \(\frac{5x}{5}=\frac{1}{5}\) - step6: Divide the numbers: \(x=\frac{1}{5}\) Solve the equation \( \left(2^{x+1} \cdot 2^{-3}\right)^{2}=2 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\left(2^{x+1}\times 2^{-3}\right)^{2}=2\) - step1: Simplify: \(2^{2\left(x-2\right)}=2\) - step2: Set the exponents equal: \(2\left(x-2\right)=1\) - step3: Divide both sides: \(\frac{2\left(x-2\right)}{2}=\frac{1}{2}\) - step4: Divide the numbers: \(x-2=\frac{1}{2}\) - step5: Move the constant to the right side: \(x=\frac{1}{2}+2\) - step6: Add the numbers: \(x=\frac{5}{2}\) The solutions to the given equations are: 1. \(5^{2x}=5^{2}\) has the solution \(x=1\). 2. \((2.5)^{2x+1}=(2.5)^{5}\) has the solution \(x=2\). 3. \(10^{1-x}=100\) has the solution \(x=-1\). 4. \(3(2.7)^{5x}=8.1\) has the solution \(x=\frac{1}{5}\) or \(x=0.2\). 5. \(\left(2^{x+1} \cdot 2^{-3}\right)^{2}=2\) has the solution \(x=\frac{5}{2}\) or \(x=2.5\).

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Extra Insights

Let's solve these equations one by one: 17. \( 5^{2x} = 5^2 \) Since the bases are the same, we can set the exponents equal to each other: \( 2x = 2 \) Dividing both sides by 2 gives us: \( x = 1 \) --- 18. \( (2.5)^{2x+1} = (2.5)^5 \) Again, since the bases are the same, we can set the exponents equal: \( 2x + 1 = 5 \) Subtracting 1 from both sides gives us: \( 2x = 4 \) Dividing by 2 results in: \( x = 2 \) --- 19. \( 10^{1-x} = 100 \) We can rewrite 100 as \( 10^2 \): \( 10^{1-x} = 10^2 \) Setting the exponents equal gives us: \( 1 - x = 2 \) Solving for \( x \): \( -x = 2 - 1 \) So, \( -x = 1 \) or \( x = -1 \). --- 20. \( 3(2.7)^{5x} = 8.1 \) First, we can divide both sides by 3: \( (2.7)^{5x} = \frac{8.1}{3} \) Calculating \( \frac{8.1}{3} \): \( (2.7)^{5x} = 2.7 \) Since the bases are the same, we can equate the exponents: \( 5x = 1 \) Dividing both sides by 5, we find: \( x = \frac{1}{5} \) --- 21. \( (2^{x+1} \cdot 2^{-3})^{2} = 2 \) Simplifying the left side, we can use exponent rules: \( 2^{(x+1) - 3} = 2^{x - 2} \) Now raising it to the power of 2: \( (2^{x - 2})^{2} = 2^{2} \) We have: \( 2^{2(x - 2)} = 2^{2} \) Equating the exponents gives us: \( 2(x - 2) = 2 \) Dividing by 2 results in: \( x - 2 = 1 \) So, \( x = 3 \). --- In summary, the solutions are: 17. \( x = 1 \) 18. \( x = 2 \) 19. \( x = -1 \) 20. \( x = \frac{1}{5} \) 21. \( x = 3 \)

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad